Design Development and Manufacture of a N95 Face Mask Making Machine - Le, Hiếu Giang; Le, Linh; Dang, Minh Phụng; Le, Hoàng Lâm; Le, Văn Hùng (Journal of Technical Education Science, 2022)
Wearing medical masks is one of the five precaution measures in the 5K message officially announced by Vietnam’s Ministry of Health. As the Covid-19 epidemic is still very complicated, a research on the design and manufacture of the qualified medical mask making machine to meet the demand for protecting ourselves from Covid-19 epidemic is vitally necessarry. Therefore, the research team focused on researching, designing and manufacturing of a N95 medical mask making machine to produce N95 masks which can prevent 95% of dust and bacteria in the air. The N95 face mask making machine is basically a N95 mask processing line consisting of 5 main clusters with a lot of design and control calculation and some details are not within the scope of this article. The current article is aimed at presenting the introduction of the machine, the operating principles, the control system parts, and the test run assessing the machine’s main features. Experimental results indicate that the machine works stably when running at low, medium and high productivity equal to or less than 2400 pieces/hour with SMS antibacterial fabric and straps made in Korea. There are some defective products when the machine operates at a productivity higher than 2400 pieces/hour. The test results also show that the stable productivity level of the machine depends on whether the materials originate in Vietnam or in Korea.